Gross Motor Deficits in Children Prenatally Exposed to Alcohol: A Meta-analysis - Lucas, B.; Latimer, J.; Pinto, R.; Ferreira, M.; Doney, Robyn; Lau, M.; Jones, T.; Dries, D.; Elliott, E. (American Academy of Pediatrics, 2014)
Background and Objectives: Gross motor (GM) deficits are often reported in children with prenatal alcohol exposure (PAE), but their prevalence and the domains affected are not clear. The objective of this review was to characterize GM impairment in children with a diagnosis of fetal alcohol spectrum disorder (FASD) or "moderate" to "heavy " maternal alcohol intake. Methods: A systematic review with meta-analysis was conducted. Medline, Embase, Allied and Complementary Medicine Database, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, PEDro, and Google Scholar databases were searched. Published observational studies including children aged 0 to =18 years with (1) an FASD diagnosis or moderate to heavy PAE, or a mother with confirmed alcohol dependency or binge drinking during pregnancy, and (2) GM outcomes obtained by using a standardized assessment tool. Data were extracted regarding participants, exposure, diagnosis, and outcomes by using a standardized protocol. Methodological quality was evaluated by using Strengthening the Reporting of Observational Studies in Epidemiology guidelines. Results: The search recovered 2881 articles of which 14 met the systematic review inclusion criteria. The subjects' mean age ranged from 3 days to 13 years. Study limitations included failure to report cutoffs for impairment, nonstandardized reporting of PAE, and small sample sizes. The meta-analysis pooled results (n = 10) revealed a significant association between a diagnosis of FASD or moderate to heavy PAE and GM impairment (odds ratio: 2.9; 95% confidence interval: 2.1-4.0). GM deficits were found in balance, coordination, and ball skills. There was insufficient data to determine prevalence. Conclusions: The significant results suggest evaluation of GM proficiency should be a standard component of multidisciplinary FASD diagnostic services.